The Prevalence of Potentially Inappropriate Prescribing in Geriatric Patients with Psychiatric Disorders in Iraq - Mahmood, Mustafa K.; Anwer, Zinah M. (Iraqi Journal of Pharmaceutical Sciences, 2020)
Potentially inappropriate prescribing is the prescribing of a medication that may cause more harm than benefit, the elderly population aged 65 years or older is more prone to potentially inappropriate prescribing because of alterations in their physiology, pharmacokinetics, and pharmacodynamics as well as polypharmacy and comorbidities, Beers list is a screening tool that help doctors to detect potentially inappropriate prescribing in geriatric patients and is designed to solve this problem, the aim of this study is to measure the prevalence of potentially inappropriate prescribing among psychiatric patients using the Beers criteria as an assessment tool and find the relationship between duration of hospitalization, comorbidities and polypharmacy with potentially inappropriate prescribing in elderly.This cross-sectional study was carried out using electronic medical records in Ibn Rushud psychiatry and addiction hospital in Baghdad and 369 patients were included. The mean age of the patients was (68.59 ± 3.75 years) and 177 (48%) of them had comorbidities, 100 (27.1%) of them had polypharmacy and 17 (4.6%) stayed in the hospital for more than 3 weeks, the most used drug classes were antipsychotics in (39.9%) of patients and benzodiazepines in (17.6%) of patients.The prevalence of potentially inappropriate prescribing according to Beers criteria was found to be 74.3% among study patients, the most prevalent inappropriately used drug class was benzodiazepines, and there was a significant association between the prescribing of a potentially inappropriate medication with gender (p=0.018), with comorbidities (p=0.022), and a very significant association with polypharmacy (p<0.001)